Secure Data: Privacy and Securing the Confidential Data with Effective Login System Using Block Chain Technology - Mrs S. Saranya,; J. Hemalakshmi,; K. Kaviya,; S. Parkavi, (International Journal of Scientific Research in Science and Technology, 2024)
As the result of technological developments and the adaption of digital system, the importance of online data transfer has grown significantly. This has resulted for the users to depend on a third party, who provides the platform to transfer the asset safely and store their sensitive data. But, it may be dangerous if the third party is not trustworthy. Many network security issues like man in middle attack, session hijack, eavesdropping, etc. can breach the confidentiality of the transaction and the data stored. Blockchain technology is meant to eliminate the sensitive issue of trust on the third party. It is a public ledger of the entire digital event that has been executed over the network. With today's world filled with information and data, it is very important for us to differentiate which information or data is authentic and which is fraudulent. Major people are facing issues like securely storing confidential data due to the increase of login credentials and also there was a problem in storing data in centralized data because the server has been hacked or affected under a malicious attack by hackers. We invent a password manager to store data in a secure format. it works under blockchain technology. Which data has been encrypted by high-level encryption namely SHA 256 algorithm and connected into chain format. Encrypted data has been stored in a decentralized server or peer-to-peer network.
Keywords: Blockchain Technology; Data Security; Confidentiality; Decentralization; Encryption; Password Manager